Penggunaan Media Pembelajaran Audiovisual Berbasis Canva untuk Meningkatkan Hasil Belajar Peserta Didik - Nuriyanti, Lina; Sudi Prayitno; Gunawan; Rahnawati (FKIP Universitas Mataram, 2025)
This research aims to determine the use of Canva-based audiovisual learning media in improving students mathematics learning outcomes. This research is classroom action research. The research was conducted in two cycles. Each cycle consists of two meetings covering the planning stages, action implementation, observation and reflection. The research subjects were students in class X.9 of SMAN 2 Mataram, totaling 36 students. The data sources used are observations, tests and learning results documents. The data analysis using quantitative descriptive analysis techniques. The results of the research show that the mathematics learning outcomes of class X.9 students at SMAN 2 Mataram have improved after use of Canva-based audiovisual learning media. These results are shown by an increase in student learning outcomes in each cycle. The increase in students learning outcomes was seen from the results of tests and observations carried out, the results had increased as indicated by the increase in the percentage of classical completeness from the pre-cycle, namely 47%, in the first cycle 75% and increased to 89% in the second cycle.